PERFORMANCE OF LOCAL GOVERNMENT INSTITUTIONS. STUDY ON BUDGET REALIZATION AND ACHIEVEMENT OF MAIN PERFORMANCE INDICATORS OF THE ENVIRONMENT SERVICE OF TOLITOLI REGENCY IN 2022 - Edi Yanto; Nurfitriana Nurfitriana; Fahri Eka Oktora (SEAN Institute, 2023)
This research is a type of descriptive research with a quantitative data analysis approach to answer problems related to the performance achievements of local government agencies through budget realization and achievement of Key Performance Indicators (IKU) of the District Environmental Service. Tolitoli in 2022. In that year DLH implemented 9 programs which were implemented in 15 activities and 35 sub-activities. The performance of the Tolitoli Regency Environmental Office showed an average achievement of 106% for 4 (four) Key Performance Indicators (IKU), which is also the goal of the regional apparatus. Based on these performance targets, a budget of Rp. 10,122,941,188, - (budget after amendment) with realized funds of Rp. 9,941,536,170, - or 98.20%. Performance achievements in 2022 show that the DLH of Tolitoli Regency has succeeded in meeting the targeted strategic objectives. This shows that the achievement of the performance of the Environment Service strategic plan for the 2021-2026 period in the second year is quite good.